Financial Support on SMEs Impact of the Covid 19 Pandemic - Gunartin Gunartin; Heri Pratikto; Sopiah Sopiah (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
The purpose of this literature review is to reveal the role of financial support for MSMEs as a result of the Covid-19 pandemic. This paper is sourced from secondary data with a review approach from the previous article. Several articles from various countries have produced that finance has a very important role in the sustainability of MSMEs. Restrictions on community activities as an effort to prevent exposure to Covid-19 impact the decline of the economy in various countries, which results in a decline in the performance of MSMEs. The decline in people's purchasing power impacts the decline in aggregate demand for goods and services, causing a decrease in income for MSME actors. Under these conditions, MSMEs need financial support from various parties for their business continuity. With financial support (capital strengthening or financing), it is hoped that MSME actors can continue their business amidst the economic crisis due to the Covid-19 pandemic. It can be concluded that financial support provides strength for MSMEs to cover operational costs and survive in conditions of economic crisis. Financial support can be in the form of disbursing stimulus funds in cash or credit, tax reductions, credit interest relief, deferral of tax payments, reduced rental fees, exemption from administrative costs to open access to financing or capital. Apart from financial support, it is also carried out to accelerate the digitization of MSMEs to open access to market expansion. Also, the women's business empowerment program (Puspa) from the East Java provincial government to increase family income.